2004
DOI: 10.1007/s00586-003-0655-3
|View full text |Cite
|
Sign up to set email alerts
|

Platelet calmodulin levels in adolescent idiopathic scoliosis (AIS): can they predict curve progression and severity?

Abstract: There is no generally accepted scientific theory for the etiology of idiopathic scoliosis. As part of its mission to widen understanding of scoliosis etiology, the International Federated Body on Scoliosis Etiology (IBSE) introduced the electronic focus group (EFG) as a means of increasing debate of extant knowledge on important topics. This has been designated as an on-line Delphi discussion. The text for this EFG was written by Professor Thomas G Lowe MD and drawn from research carried out by himself and his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 18 publications
0
49
0
6
Order By: Relevance
“…Elevated platelet calmodulin levels are found in children with progressive scoliosis. 64,65 Current controversy focuses on the lack of control data and the large variability of baseline platelet calmodulin levels in idiopathic scoliosis patients. 66 For the purpose of clinical neuromotor assessment of children with idiopathic scoliosis, MRIs of the brain and spinal cord can help in the investigation of abnormalities of proprioception, postural equilibrium control, oculovestibular function, and vibratory sensation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated platelet calmodulin levels are found in children with progressive scoliosis. 64,65 Current controversy focuses on the lack of control data and the large variability of baseline platelet calmodulin levels in idiopathic scoliosis patients. 66 For the purpose of clinical neuromotor assessment of children with idiopathic scoliosis, MRIs of the brain and spinal cord can help in the investigation of abnormalities of proprioception, postural equilibrium control, oculovestibular function, and vibratory sensation.…”
Section: Discussionmentioning
confidence: 99%
“…64,65 Current controversy focuses on the lack of control data and the large variability of baseline platelet calmodulin levels in idiopathic scoliosis patients. 66 For the purpose of clinical neuromotor assessment of children with idiopathic scoliosis, MRIs of the brain and spinal cord can help in the investigation of abnormalities of proprioception, postural equilibrium control, oculovestibular function, and vibratory sensation. [67][68][69][70][71] Younger children with progressive idiopathic scoliotic curves with and without neuromotor signs are more likely to have brain stem abnormalities such as Arnold-Chiari type-1 malformation, syringomyelia, or cerebellar tonsillar ectopia.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a study in 55 AIS patients confirmed a direct relationship between higher platelet calmodulin levels and curve progression. Furthermore, curve stabilization by bracing or spine fusion reduced these levels in 82 and 90 % of patients, respectively [31]. In a controlled clinical study, AIS patients were shown to display an asymmetric distribution of calmodulin levels in paraspinal muscle, higher at the convex side and lower at the concave [1].…”
Section: Melatoninmentioning
confidence: 99%
“…5 Rotation movements of the body test-comparison of the left and right rotation movement of the pelvis and shoulders (whole body) in "standing straight position" of the child with feet close together [38][39][40][41][42][43][44][45][46][47][48][49].…”
mentioning
confidence: 99%